Socioeconomic inequalities in non-communicable diseases in South Africa - Zulu, Tryphine (Department of Public Health and Family Medicine, 2020)
Non-communicable diseases (NCDs) have reached epidemic proportions globally and in South Africa. This thesis is situated within the health equity framework. The aim is to assess the extent of wealth related inequalities in NCDs and to assess the impact of the social determinants of health in mediating these inequalities. Data from the first South African National Health and Examination Survey (SANHANES-1) and wave 4 of the South African National Income Dynamics Study (NIDS) were used. The methods used include the concentration curve, concentration index and decomposition analysis to assess the drivers of socioeconomic inequality in NCDs and some causes of NCDs including smoking, obesity, high blood pressure; use of screening services and effective coverage for hypertension management. The prevalence of smokers is 18.7%, the population average BMI is 26.38 kg/m2, and the prevalence of hypertension is 29.7%. The distribution of these risk factors is pro-wealthy with concentration indices ranging from 0.048 for hypertension, 0.057 for smoking prevalence to 0.115 for obesity. While these risk factors are prevalent amongst the wealthy, the outcomes are worse amongst the poor. The concentration index for expenditure on cigarettes is strongly pro-poor, (-0.130) compared to the prowealthy smoking prevalence. The hypertensive poor suffer more severe hypertension with a concentration index of -0.054 for depth and -0.079 for severity, respectively. Obesity affects the wealthiest the most. However, the overweight adults who are poor tend to suffer more severe obesity as shown by a relatively smaller concentration index of depth (0.015) and severity (0.033) respectively. The overall utilisation of screening services is below 50% for eligible respondents. The two wealthiest quintiles benefit disproportionately more than they should, given their share of the population. This is particularly true for diabetes and cholesterol with a concentration index of 0.27 for cholesterol, 0.129 for diabetes and 0.052 for hypertension. Adults that do not take up screening services are predominantly the black race group, poor, rural, male, unemployed and uninsured. Only 23% of those with hypertension are diagnosed, on treatment and are controlled. Wealth-related variables such as education, wealth, health insurance coverage and province of residence drive most of the observed pro-wealthy inequalities in this thesis. Wealthier adults benefit to a larger extent from the care cascade, compared to the poor. Therefore, until there is a substantial increase in early diagnosis and effective treatment, high levels of mortality from NCDs will persist in South Africa. And until the poor are prioritised through radical policy change in all economic sectors, the observed inequalities will continue.